Numerical Simulation of Surface Thermal Analysis and Cooling Optimization of Continuous Casting Rolls - Guangwei Cheng; Ningxia Yin; Qiaoxin Zheng; Yuming Qiu; Junqi Chen (Crystals)
In many steel mills, the working life of continuous casting machine rollers is relatively short, requiring frequent replacement and negatively impacting production efficiency. To effectively extend the service life of these rollers, this study focuses on a continuous casting machine at a steel mill in China. A numerical simulation was conducted, revealing that the rollers in contact with the high-temperature casting billet experience significant thermal and stress impacts. The traditional cooling channel struggles to sufficiently reduce both the surface temperature and stress, resulting in severe thermal fatigue damage to the roller surfaces. Observations of roller surface wear showed signs of adhesive wear, fatigue cracks, and spalling occurring in various regions of the roller, which aligned with the stress distribution predicted by the simulation. In response, the cooling channel structure was modified to enhance the cooling effect of the water. Optimization of both the cooling channel structure and its parameters was carried out using a coupled flow-heat-force numerical simulation method. The optimized cooling channel effectively improved the working condition of the continuous casting roll, as the maximum temperature of the roll surface was reduced from 810 K to 591 K, the circumferential temperature difference was reduced by 38%, and the maximum equivalent stress decreased from 791 MPa to 558 MPa. This adjustment also resulted in a more uniform surface temperature distribution, mitigating the sudden fluctuations in normal stress that are typical of conventional rollers.